2015
DOI: 10.1089/jmf.2015.3439
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside Ameliorates Hepatic Metaflammation by Modulating NLRP3 Inflammasome in a Rodent Model of Type 2 Diabetes

Abstract: Low-grade chronic inflammation (metaflammation) is a major contributing factor for the onset and development of metabolic diseases, such as type 2 diabetes, obesity, and cardiovascular disease. Nicotinamide riboside (NR), which is present in milk and beer, is a functional vitamin B3 having advantageous effects on metabolic regulation. However, the anti-inflammatory capacity of NR is unknown. This study evaluated whether NR modulates hepatic nucleotide binding and oligomerization domain-like receptor family, py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 41 publications
6
43
0
Order By: Relevance
“…NAFLD is characterized by metabolic derangement, insulin resistance, oxidative stress, and inflammation. KK/ HlJ mice fed a high fat diet showed hepatocyte injury and hepatic triglyceride accumulation, which are typical histopathological features of NAFLD (Ikejima et al 2007;Chen et al 2010;Lee et al 2015). Similar to the previous study, we also observed adipose infiltration and liver tissue structural damage in this study; however, RHL was able to improve the effects of this damage.…”
Section: Discussionsupporting
confidence: 90%
“…NAFLD is characterized by metabolic derangement, insulin resistance, oxidative stress, and inflammation. KK/ HlJ mice fed a high fat diet showed hepatocyte injury and hepatic triglyceride accumulation, which are typical histopathological features of NAFLD (Ikejima et al 2007;Chen et al 2010;Lee et al 2015). Similar to the previous study, we also observed adipose infiltration and liver tissue structural damage in this study; however, RHL was able to improve the effects of this damage.…”
Section: Discussionsupporting
confidence: 90%
“…ROS promotes the dissociation of thioredoxin-interacting protein (TXNIP) from thioredoxin and allows TXNIP to bind to NLRP3, and subsequently stimulates NLRP3 activation in mouse beta cells [18]. It is now well recognized that the NLRP3 inflammasome is implicated in the pathophysiology of a number of diseases, including depression [19], type 2 diabetes [20], rheumatoid arthritis [21] and Alzheimer's disease [22]. Thus, the functional manipulation of the NLRP3 inflammasome has been thought to be a promising therapeutic strategy for these diseases [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…The changes found in disease-free animals in our current and previous studies (Elamin et al, 2017) indicate that the use of ketone bodies as an energy source can be associated with a healthier metabolic phenotype and an enhanced redox state even in the absence of disease or senescence. Furthermore, the NAD + precursor nicotinamide ribose and PARP inhibitors are proposed to combat cancer and a host of inflammatory and neurodegenerative diseases (Basello and Scovassi, 2015; Lee et al, 2015; Ohmoto and Yachida, 2017; Vaur et al, 2017). We provide evidence that consuming a KD can mobilize similar mechanisms, and promote the metabolic resilience necessary to combat neurodegenerative and age-associated diseases.…”
Section: Discussionmentioning
confidence: 99%